Advances in basic and clinical research of the comorbidity of epilepsy and migraine - Jian WANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2019)
Epilepsy is a chronic brain dysfunction syndrome caused by abnormal discharge of neurons in the brain induced by various causes. Migraine is a chronic neurovascular disease characterized by unilateral or bilateral paroxysmal headache. Epilepsy and migraine are both paroxysmal, transient, repetitive and stereotyped. Comorbidity of epilepsy and migraine refers to the occurrence of non-causal relationship between the two disorders in the same patient. The incidence of epilepsy in patients with migraine and the incidence of migraine in patients with epilepsy are higher than that in general population. This article will review the latest advances of pathogenesis, diagnosis and treatment of epilepsy and migraine comorbidity, so as to help clinicians deepen the understanding of the comorbidity.